2010
DOI: 10.14214/sf.121
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of growth responses of Khaya senegalensis seedlings and stecklings to four irrigation regimes

Abstract: Khaya senegalensis is an important tree species for timber production, native to West Africa, but mahogany shoot borer attacks prevent successful plantations. This research was aimed at comparing the growth of two propagule types, seedlings and stecklings, of Khaya senegalensis subjected to four irrigation regimes, 25, 50, 75 and 100% field capacity in Burkina Faso. The relative growth rate, biomass allocation and intrinsic water use efficiency of the propagules were assessed in a full-factorial pot experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
3
2
0
1
Order By: Relevance
“…Seedlings of P. nitida which received the lowest water rate (10 ml) at the longest intervals of 5 days had the lowest biomass value, this agreed with the findings of several authors that drought water stress influences plant growth and limits productions (Ky-Dembele et al, 2010;Hsiao & Xu, 2000;Busso et al, 1998;Hampson & Simpson, 1990). In this study, excess of water alsohad negative impact on growth and biomass production of the seedlings.This result agreed with the findings of Sakio (2005) that flooding reduces the total dry weight increment in some plant species.In flooding condition, available oxygen in the soil is usually low thus, limiting nutrient absorption for species not adapted to this condition; and as stated by Predick et al (2009) growth of flood-intolerant species is often depressed in flooding.…”
Section: Net Assimilation Rate (Nar)supporting
confidence: 92%
“…Seedlings of P. nitida which received the lowest water rate (10 ml) at the longest intervals of 5 days had the lowest biomass value, this agreed with the findings of several authors that drought water stress influences plant growth and limits productions (Ky-Dembele et al, 2010;Hsiao & Xu, 2000;Busso et al, 1998;Hampson & Simpson, 1990). In this study, excess of water alsohad negative impact on growth and biomass production of the seedlings.This result agreed with the findings of Sakio (2005) that flooding reduces the total dry weight increment in some plant species.In flooding condition, available oxygen in the soil is usually low thus, limiting nutrient absorption for species not adapted to this condition; and as stated by Predick et al (2009) growth of flood-intolerant species is often depressed in flooding.…”
Section: Net Assimilation Rate (Nar)supporting
confidence: 92%
“…Later on, glucose is broken, which through respiration produces ATP to support the growth of the root system. The results of this study corroborate those found by Ky-Dembele et al (2010), who found greater root system growth when assessing growth responses of K. senegalensis under water deficit and Okali and Dodoo (1973) reported the reduction of perspiration and increase in the partitioning of assimilates to the root system of plants K. senegalensis.…”
Section: Discussionsupporting
confidence: 91%
“…Similar results of drought responses on the growth characteristics have been reported in several previous studies (Yang and Miao, 2010;Ky-Dembele et al, 2010). Water deficits reduce the number of leaves per plant, and individual leaf size, and leaf longevity by decreasing the soil's water potential.…”
Section: Growth Characteristics and Biomass Productionsupporting
confidence: 88%